The Old-Age Reserve Fund is not "Illusory" - Robinson, George Buchan (Quarterly Journal of Economics, 1945)
Dr. Lutz's argument, 136; — I. Important distinctions neglected, 137. — II. Unacceptable distinctions made, 139. — III. Purpose of the fund misunderstood, 142. — IV. Separate entity of the pension program not essential to the argument, 145. — V. Taxation for liquidation of fund is not for social security, 146. — VI. Importance of upholding the Government's credit, 149. — VII. The question of accumulation must be considered on its merits, 151.